Anisotropic electron populations in BL Lac jets: consequences for the observed emission. Issue 2 (14th November 2019) - Tavecchio, F; Sobacchi, E
ABSTRACT: We investigate the impact on the properties of high-energy emitting BL Lacertae (BL Lac) objects of a population of electrons with an anisotropic momentum distribution. We adopt a simple phenomenological description of the anisotropy, in which the most energetic electrons have a small pitch angle and the least energetic electrons are isotropic, as proposed by Sobacchi & Lyubarsky. We explore (i) a simple model that assumes a phenomenological shape for the electron energy distribution, and (ii) a self-consistent scheme in which the electrons follow a distribution that is the result of the balance between injection and radiative losses (we include the effects of the anisotropy on the synchrotron cooling rate). Considering the BL Lac object Mrk 421 as representative of the entire class, we show that in both cases the emission can be satisfactorily reproduced under equipartition between the magnetic field and the relativistic electrons. This is in better agreement with the idea that jets are launched as Poynting-dominated flows with respect to the standard isotropic scenario, which requires both a low magnetization and a low radiative efficiency to reproduce the observed emission. The hard spectrum predicted for the inverse Compton continuum at TeV energies could be used as a potential test of the anisotropic model.